Рекламна стаття як вид інформаційного матеріалу - Сінюченко, Олеся О.; Sinyuchenko, O. O. (Східноєвропейський національний університет імені Лесі Українки, 2014)
Автор намагається проаналізувати роль та місце рекламної статті як виду рекламного матеріалу, проводить паралелі між інформаційними, аналітичними та рекламними статтями, характеризує особливості рекламних статей, їх значення в сучасному світі. З’ясовано засоби привернення уваги аудиторії до рекламних матеріалів. Виокремлено основні критерії написання рекламної статті як публікації інформаційно-розважального характеру. The author attempts to analyze the role and place of promotional articles as a form of advertising material, draws parallels between information, analytical and promotional items, the features of promotional items, their importance in the modern world. Given the qualitative impact of media on society and attitudes to advertising, advertisers and piarmeny invent new ways to feed more advertising and means of implementation. One of the innovations is the advertising article. Advertising article may be similar to conventional advertising is not sex. This followed basics of marketing problems of any advertising – bringing hidden ideas to the recipient. For this corresponds to a number of specific performance indicators promotional articles as a means of implementing new ideas: the depth and duration of exposition presence variety of topics, improving the process of printing and more. Writing, advertising text – an opportunity available and clearly tell the reader about the specific benefits of purchasing the product, to form a certain attitude and the right motivation to encourage consumption of the product or service.
Advertising Article as a Form of Information Material
Keywords: реклама; advertisement; рекламна діяльність; advertising; рекламна стаття; promotional articles; рекламний текст; advertising text; аудиторія; audience